Manifestation of stylistic devices in German media texts on Ukraine crisis - Pochapska, Olha (Lviv Polytechnic Publishing House, 2015)
The paper attempts to describe stylistic peculiarities of modern media text. The articles for research were chosen from the German newspaper; they cover the events in the east of Ukraine which are known in the western mass media as Ukraine Crisis. As a result, this study raises a question: how the application of stylistic devices is connected with the function of media texts.
Keywords: media linguistics; media text; news coverage; stylistics; stylistic devices; Ukraine crisis